Optimization of photodecomposition of chelatic Complex Phenyl hidrazedo-tris (diethyl dithiocarbamato) Molybdenum )V( - Habeeb, Hassan A.; Hussain, Nadia B. (Al-Qadisiyah Journal of Pure Science, 2017)
In this study the complex Phenyl hydrazido – tris – diethyldithiocarbato – molybdenum(V)[Mo(N2ph)(S2CNEt2)3] was prepared and identified by (UV-Visible) and infrared (FTIR) spectroscopy. The kinetics of chemical decomposition for this chelatic structure was studied by using irradiation of this complex solution, by using a mono wave light (λ=365nm) and temperature (25C˚) for (60 min) in ethanol solvent. The order of the photochemical decomposition was the first order reaction, As well as the rate constant of photo decomposition reaction (kd) was calculated by observed the spectral changes during the irradiation process. To know the best conditions for decomposition of this compound complex, it is necessary to study the effect of several factors on the photo chemical behavior for the complex which included: Effect of concentration of the complex, where five concentrations of the complex have been studied and found that the highest decomposition rate have observed at concentration (2.5*10-5M). In addition, the impact of the change in the intensity of the light on decomposition rate was studies show that the result when the light intensity increase, the rate of the complex decomposition also increased. Also the complex decomposition at the temperature range (20-35Cº) was studied. When increasing the temperature increases the rate of the complex decomposition . The effect of pH value at the range 3-11 and found that the rate of the complex decomposition increased when pH of the solution increases. The effect of four alcoholic solvent were studied (methanol, ethanol, isopropanol and 1- butanol), and found that the highest decomposition rate of the complex achieved in Methanol, while the lowest decomposition rate of the complex achieved in Isopropanol. In addition the effect of each of nitrogen gas, oxygen gas and the atmospheric air on the the rate of complex decomposition was studied and compile the results with recorded results in normal conditions, the highest decomposition rate observed in the presence of oxygen gas and the lowest decomposition in the presence of nitrogen gas. The mechanism of photo chemical decomposition of the complex has been interpreted by spectrophotometric technique, were the conclusion that have been obtained that there is (redox- reaction) happening in this complex and the output of the processes of homo cleavage of (M-L) bond that leading to reduction of metal ions and oxygenation of ligand and formation free radicals .